DIRECTIONS FOR EFFECTIVE USE OF PROPERTY TAX IN EXPANDING THE TAX BASE - Sharopov Dilshodjon Rakhmatullaevich (The Conference Hub, 2025)
This thesis analyzes the role and significance of property tax in expanding the tax base. It highlights opportunities to increase budget revenues through property tax, current challenges, and measures to address them. Effective approaches such as digitalization, market value-based assessment, review of exemptions, and the introduction of a progressive tax rate system are proposed. The findings of this study contribute to further improving the tax policy of our country.
Keywords: property tax, tax base, tax exemptions, digitalization, market value, automated valuation, progressive rate, local budget, tax policy, economic efficiency.